Nodo de distribución urbana de transporte para pasajeros trígono (2019)
Given the problem, facing the mobility system in the urban areas of the city, Bogotá Girardot, an intermodal transport is proposed, in the municipality of Soacha, to prevent passenger buses from entering the city of Bogota and thus avoid the collapse of the road structure, which brings with it high CO2 emissions, pirate transport, informal commerce, insecurity. Etc.